2011
DOI: 10.1371/journal.pone.0027008
|View full text |Cite
|
Sign up to set email alerts
|

MiR-223 Suppresses Cell Proliferation by Targeting IGF-1R

Abstract: To study the roles of microRNA-223 (miR-223) in regulation of cell growth, we established a miR-223 over-expression model in HeLa cells infected with miR-223 by Lentivirus pLL3.7 system. We observed in this model that miR-223 significantly suppressed the proliferation, growth rate, colony formation of HeLa cells in vitro, and in vivo tumorigenicity or tumor formation in nude mice. To investigate the mechanisms involved, we scanned and examined the potential and putative target molecules of miR-223 by informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
105
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 28 publications
4
105
1
1
Order By: Relevance
“…Thus, we could also speculate that miR-223 downregulation can also lead to increased KLF5 expression observed in PAH (8). Moreover, downstream miR-223 targets IGF-1R and HSP90␤ seem to act on proliferation through the phosphatidylinositol 3-kinase, Akt, and mammalian target of rapamycin (PI3K/Akt/ mTOR) pathway (13,18) known to play a role in PAH pathophysiology (10,26,36).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, we could also speculate that miR-223 downregulation can also lead to increased KLF5 expression observed in PAH (8). Moreover, downstream miR-223 targets IGF-1R and HSP90␤ seem to act on proliferation through the phosphatidylinositol 3-kinase, Akt, and mammalian target of rapamycin (PI3K/Akt/ mTOR) pathway (13,18) known to play a role in PAH pathophysiology (10,26,36).…”
Section: Discussionmentioning
confidence: 97%
“…Other downstream targets of miR-223 not explored in the current study might also contribute to PAH development including F-box and WD repeat domain-containing 7 (FBW7), insulin-like growth factor 1 receptor (IGF-1R), and heat shock protein 90␤ (HSP90␤), as they all play a role in cell proliferation and apoptosis in cancer (13,18,38), which share many similarities with PAH (31). Wang et al (38) demonstrated that miR-223 is a repressor of FBW7, which regulates Kruppel-like factor 5 (KLF5) expression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that upregulation of miR-223 is associated with the pathophysiology of infection, inflammation and cancer (30). An in vitro study indicated that miR-223 downregulated the IGF-1 receptor and inhibited cell proliferation (10). In addition, the serum IGF-1 level increased in patients with MSA and is associated with disease progression (9).…”
Section: Discussionmentioning
confidence: 99%
“…Since IGF-1 signaling has been revealed to be regulated by several miRNAs (10,11), it may be hypothesized that miRNAs and IGF-1 contribute to the pathogenesis of MSA.…”
Section: Introductionmentioning
confidence: 99%
“…IGF-1R activates multiple downstream signaling cascades, including PI3K/AKT and MAPK/ERK signaling pathways, which regulate cell proliferation, differentiation, and survival (Baserga et al 2003;Cao et al 2007). More recently, several miRNAs, such as miR-7, miR-145, miR-223, and miR-375, have been reported to negatively regulate IGF-1R (Shi et al 2007;Jia et al 2011;Kong et al 2012;Zhao et al 2012), suggesting that miRNAs targeting IGF-1R have an important role in carcinogenesis and are potential therapeutic agents for human cancer.…”
Section: Introductionmentioning
confidence: 99%